MENGEMBANGKAN KECERDASAN INTRAPERSONAL MELALUI MEDIA KARTU EKSPRESI PADA ANAK USIA DINI - Nanda Syavira; Artika Seprina, Annisa Fitri Handayani, Pikawati Habeahan, Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Intrapersonal intelligence is also the ability to understand oneself, know who one is, what one wants to do and how oneself reacts to situations such as what one should avoid as well as directing and introspecting oneself. The aim of this research is to uncover favorite pocket media. The research method used is literature study. The type of data source used by researchers is secondary source data. The data collection technique used was from several relevant previous book and journal data according to the problem topics raised by the researcher. Based on the data from several findings that have been carried out by researchers, it can be concluded that the favorite pocket game has an effect on the intrapersonal intelligence of young children.